1989
DOI: 10.1104/pp.90.4.1440
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Low Cl Concentrations in Mesophyll Cells of Leaf Blades of Barley Seedlings Exposed to Salt Stress

Abstract: The concentrations of vacuolar Na+ and Cl-in the epidermal and mesophyll cells of the leaf blade and sheath of Hordeum vulgare seedlings (cv California Mariout and Clipper) were measured by means of quantitative electron probe x-ray microanalysis. A preferential accumulation of Cl-in vacuoles of epidermial cells in both blade and sheath and a low level in mesophyll cells of the blade were evident in plants grown in full strength Johnson solution. The concentration of Cl-in the mesophyll cells of the blade rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 16 publications
6
25
0
Order By: Relevance
“…− to epidermal cells in both durum wheat and barley, particularly at low leaf Cl − concentrations (50-150 mM), is consistent with the findings of other studies using salt-stressed barley (Huang & van Steveninck 1989;Leigh & Storey 1993;Fricke et al 1996). This reproducible pattern of epidermal Cl − deposition has also been established in non-saline conditions (Huang & van Steveninck 1989;Fricke et al 1996), and additionally, Karley et al (2000a) found significant Cl − partitioning in the isolated epidermal protoplasts of young barley leaves in control conditions.…”
Section: Preferential Partitioning Of CLsupporting
confidence: 90%
See 3 more Smart Citations
“…− to epidermal cells in both durum wheat and barley, particularly at low leaf Cl − concentrations (50-150 mM), is consistent with the findings of other studies using salt-stressed barley (Huang & van Steveninck 1989;Leigh & Storey 1993;Fricke et al 1996). This reproducible pattern of epidermal Cl − deposition has also been established in non-saline conditions (Huang & van Steveninck 1989;Fricke et al 1996), and additionally, Karley et al (2000a) found significant Cl − partitioning in the isolated epidermal protoplasts of young barley leaves in control conditions.…”
Section: Preferential Partitioning Of CLsupporting
confidence: 90%
“…This reproducible pattern of epidermal Cl − deposition has also been established in non-saline conditions (Huang & van Steveninck 1989;Fricke et al 1996), and additionally, Karley et al (2000a) found significant Cl − partitioning in the isolated epidermal protoplasts of young barley leaves in control conditions. Leigh & Tomos (1993) concluded that the distribution of Cl − into the epidermis was a likely result of preferential Cl − movement through the vein extension apoplast.…”
Section: Preferential Partitioning Of CLsupporting
confidence: 66%
See 2 more Smart Citations
“…However, it is now becoming clear that solutes are also differentially distributed between different cell types in leaves and that these intercellular solute distributions may also respond to changes in nutrient availability (see review by Leigh and Tomos 1993). For instance, studies of barley leaves using either protoplast isolation (Dietz et al 1992b) or energy-dispersive X-ray (EDX) microanalysis of bulk-frozen hydrated sections (Leigh et al 1986;Huang and van Steveninck 1989;Williams et al 1991;Leigh and Storey 1993) have shown that P is largely restricted to mesophyll cells and is virtually indetectable in epidermal cells while the reverse is true for Ca. Other solutes such as K or Na are more-evenly distributed between the two cell types.…”
Section: Introductionmentioning
confidence: 98%